2022
DOI: 10.3390/bios12080622
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Biosensor for SARS-CoV-2 cDNA Detection Using AuPs-Modified 3D-Printed Graphene Electrodes

Abstract: A low-cost and disposable graphene polylactic (G-PLA) 3D-printed electrode modified with gold particles (AuPs) was explored to detect the cDNA of SARS-CoV-2 and creatinine, a potential biomarker for COVID-19. For that, a simple, non-enzymatic electrochemical sensor, based on a Au-modified G-PLA platform was applied. The AuPs deposited on the electrode were involved in a complexation reaction with creatinine, resulting in a decrease in the analytical response, and thus providing a fast and simple electroanalyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…The use of PLA with graphene has been reported in many studies. [43][44][45][46][47][48] It has been reported that most of them used dimethylformamide (DMF), NaOH, and sulfuric acid treatment for the surface modication. Table 1 shows the different types of materials that are used in 3D printing with their surface modication techniques and applications.…”
Section: Plamentioning
confidence: 99%
“…The use of PLA with graphene has been reported in many studies. [43][44][45][46][47][48] It has been reported that most of them used dimethylformamide (DMF), NaOH, and sulfuric acid treatment for the surface modication. Table 1 shows the different types of materials that are used in 3D printing with their surface modication techniques and applications.…”
Section: Plamentioning
confidence: 99%
“…A facile, non-enzymatic electrochemical sensor for the detection of SARS-CoV-2 cDNA was developed by Silva et al [62] using a disposable, low-cost graphene polylactic (G-PLA) 3D-printed electrode modified with Au nanoparticles. Through a complex reaction with creatinine, the Au nanoparticles that were deposited on the electrode facilitated a reduction in the analytical response, leading to the development of a fast and straightforward electroanalytical device.…”
Section: Using Graphenementioning
confidence: 99%
“…[3] Electrochemical detection has shown great promise to address the limitations of molecular spectroscopic approaches. A variety of electrochemical biosensors [4] have been developed for the detection of SARS-CoV-2, encompassing immunosensors, [5] aptasensors, [6] and enzymatic [7] sensors. These sensors utilize diverse platforms and substrates such as screenprinted electrodes (SPEs), [8] paper-based systems, [9,10] gold electrodes, [11] test strips, [12] and others, demonstrating rapid and accurate detection of SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%